Immune Response toward Mycobacterium Tuberculosis Infection - Ikram Hasanuddin, Abdi Dzul; Roswita, Nanang; Virnanda Amu, Ivan (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Understanding the human immune response toward Mycobacterium tuberculosis infection is important for controlling its infection. Its transmission through the air consists of